Positive Correlation between Normal Serum Gastrin Concentrations and Antral and Duodenal G Cells. (1st August 1994) - Yacoub, WR; Thomson, ABR; Sherbaniuk, RW; Hooper, P; Jewell, LD
Abstract : It is controversial whether there is a correlation between serum gastrin concentrations and the density of G cells in the antral or duodenal mucosa. In this study, endoscopically obtained antral and duodenal biopsies were stained immunocytochemically for gastrin and the G cells quantitated using an MOP Videoplan computer image analysis system. Studies were performed in 20 patients with acid-peptic disorders (gastric ulcer, n=5; duodenal ulcer, n=10; reflux esophagitis, n=4; and nonulcer dyspepsia, n=1). Correlations between antral and duodenal G cell densities, and basal- and food-stimulated serum gastrin concentrations within the normal range (less than 100 mg/L) – but not in those with elevated gastrin concentrations – support the postulate that alterations in G cell function are important in patients with acid-peptic disorders.